Distinct Molecular Effects of Angiotensin II and Angiotensin III in Rat Astrocytes. (14th February 2013) - Clark, Michelle A.; Nguyen, Chinh; Tran, Hieu
Abstract : It is postulated that central effects of angiotensin (Ang) II may be indirect due to rapid conversion to Ang III by aminopeptidase A (APA). Previously, we showed that Ang II and Ang III induced mitogen-activated protein (MAP) kinases ERK1/2 and stress-activated protein kinase/Jun-terminal kinases (SAPK/JNK) phosphorylation in cultured rat astrocytes. Most importantly, both peptides were equipotent in causing phosphorylation of these MAP kinases. In these studies, we used brainstem and cerebellum astrocytes to determine whether Ang II's phosphorylation of these MAP kinases is due to the conversion of the peptide to Ang III. We pretreated astrocytes with 10  μ M amastatin A or 100  μ M glutamate phosphonate, selective APA inhibitors, prior to stimulating with either Ang II or Ang III. Both peptides were equipotent in stimulating ERK1/2 and SAPK/JNK phosphorylation. The APA inhibitors failed to prevent Ang II- and Ang III-mediated phosphorylation of the MAP kinases. Further, pretreatment of astrocytes with the APA inhibitors did not affect Ang II- or Ang III-induced astrocyte growth. These findings suggest that both peptides directly induce phosphorylation of these MAP kinases as well as induce astrocyte growth. These studies establish both peptides as biologically active with similar intracellular and physiological effects.